Study of Exploitation of Marine Ornamental Fish by Utilizing Artificial Reefs as A Solution for Coral Reef Rehabilitation in Barru Regency - Syatir Suaib; Muh. Nadir (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This study aims to determine the diversity of marine ornamental fish species found in natural coral reefs and artificial reefs. This research is descriptive in nature, data collection was carried out by observation or direct observation in the field by catching using nets and sero every 4 days for three months at coral reef and artificial reef locations. The catch is recorded based on the location of the catch. In this study, an artificial reef was created with a concrete construction design in the form of rectangular blocks/boxes. The types of fish caught on natural coral reefs are the parrot fish in the Scaridae family, Triger fish in the Balistidae family, Titang fish in the Acanturidae family and Lepu fish in the Scorpaenidae family. Types of fish caught on artificial reefs are; Bracelet giru, Giru striped, waru flower, Sekar spurs, Lencan, Peperek, Tompel, Betok sebra and Triger